Changes [large type] : a novel of the Dresden files - Butcher, Jim, 1971- (Butcher, Jim, 1971- Dresden files., 2010)
Long ago, Susan Rodriguez was Harry Dresden's lover, until she was attacked by his enemies, leaving her torn between her own humanity and the bloodlust of the vampiric Red Court. Susan disappeared to South America, where she could fight both her savage gift and those who cursed her with it. Now Arianna Ortega, Duchess of the Red Court, has discovered a secret that Susan has long kept, and she plans to use it against Harry.